RISK PREDICTION OF CORONARY ARTERY DISEASE WITH OR WITHOUT DIABETES MELLITUS: APOLIPOPROTEINS SCORE OVER LIPID FRACTIONS. - NOORJAHAN MOHAMMED; AMBIKA DEVI.K; RAMARAO JANYAVULA; BHASKAR RAJU.D.S; SAI BABA SS KOMPELLA (International Journal of Pharma and Bio Sciences, 2014)
To evaluate the association of lipoproteins & apolipoproteins with Coronary artery disease (CAD) in patients with (CAD-DM+) & without Type II Diabetes mellitus (CAD-DM-) and to determine better risk predictor, we conducted a case-control study. 40 patients with clinical and angiographic evidence of CAD (20 diabetics, 20 non-diabetics) and 20 healthy controls were drawn for the study. Significantly high total cholesterol(TC), Triglycerides(TG), low density cholesterol(LDL-C), TC/HDL-C were observed in CAD-DM+ patients but no significant differences were found in CAD-DM- patients when compared with controls. On the other hand, levels of ApoB/A-I(apolipoproteinB/ apolipoproteinA-I) and apoB were significantly high in both groups. When comparison was done between two CAD groups, significantly higher(p<0.001) levels of ApoB/A-I and apoB were observed in diabetics compared to non-diabetics. In ROC analysis between CAD-DM+ vs. controls, maximum AUC was found for apoB/A-I(0.9975) and apoB(0.9925) compared to LDL-C(0.8425), TC/HDL-C(0.7913). Between CAD-DM- and controls, AUC for apoB/A-I(0.81) was maximum compared to apoB(0.6575), LDL-C(0.6313) and TC/HDL-C(0.5613). These findings suggest that ApoB/A-I is a better predictor of risk for CAD whether associated with DM or not, and is superior to traditional lipid markers in patients without DM.